Combinatorial asymmetric acoustic metamaterials with real-time programmability - Melanie R. Keogh; Osama R. Bilal (Proceedings of the National Academy of Sciences, 2025)
Metamaterials can stretch the envelope of attainable material properties giving rise to negative effective dynamical parameters. Metamaterials usually achieve such superior functionality through hard-coded geometry, symmetry, and periodicity that cannot be altered postfabrication. While a great deal of research is dedicated to tunable metamaterials, the ability to tune metamaterials on-the-fly in a scalable manner remains an open challenge. Here, we introduce a real-time programmable, combinatorial metamaterial framework composed of asymmetric pillars that can manipulate acoustic waves based on the pillars’ angular orientation. First, we demonstrate the utility of our metamaterials with all pillars oriented in the same direction, exhibiting wave attenuation, localization, and topological insulation. Subsequently, we expand the unit-cells into multiple domains and supercells where the number of possible designs enlarges to exceed 10 100 . Our metamaterials offer real-time programmability at both the unit-cell level using individual motors for high versatility, and at a functional domain level using gears for simplicity. We also present a hybrid approach combining motors and gears in clusters providing a balance between versatility and simplicity. We expect our scalable, combinatorial approach with on-demand reprogrammability of acoustic properties to facilitate the development of advanced forms of acoustic devices.